THE ROLE OF CEFR IN STANDARDIZING ENGLISH LANGUAGE ASSESSMENT WORLDWIDE - Izzatullayeva Nozimakhon Elmurod kizi (NAZARIY VA AMALIY FANLARDAGI USTUVOR ISLOHOTLAR VA ZAMONAVIY TA'LIMNING INNOVATSION YO'NALISHLARI, 2025)
This article provides an expanded and paraphrased analysis of the role of the Common European Framework of Reference for Languages (CEFR) in the global standardization of English language assessment. CEFR functions as an internationally accepted benchmark that ensures consistency, transparency, and comparability in evaluating English language proficiency. The paper explores the conceptual basis of CEFR, its proficiency scale, and its practical application in international testing systems. Furthermore, it examines how CEFR contributes to quality assurance in language assessment while addressing contemporary challenges related to contextual adaptation and test alignment. The study highlights that CEFR, despite certain limitations, remains a key instrument for harmonizing English language assessment practices worldwide.